Shear-Enhanced Transfer Printing of Conducting Polymer Thin Films - Sen, Pratik; Xiong, Yuan; Zhang, Qianqian; Park, Sungjune; You, Wei; Ade, Harald; Kudenov, Michael W; O’Connor, Brendan T (ACS applied materials & interfaces, 2018)
Polymer conductors that are solution-processable provide an opportunity to realize low-cost organic electronics. However, coating sequential layers can be hindered by poor surface wetting or dissolution of underlying layers. This has led to the use of transfer printing where solid film inks are transferred from a donor substrate to partially fabricated devices using a stamp. This approach typically requires favorable adhesion differences between the stamp, ink, and receiving substrate. Here, we present a shear-assisted organic printing (SHARP) technique that employs a shear load on a post-less polydimethylsiloxane (PDMS) elastomer stamp to print large-area polymer films that can overcome large unfavorable adhesion differences between the stamp and receiving substrate. We explore the limits of this process by transfer printing poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) films with varied formulation that tune the adhesive fracture energy. Using this platform, we show that the SHARP process is able to overcome a 10-fold unfavorable adhesion differential without the use of a patterned PDMS stamp, enabling large-area printing. The SHARP approach is then used to print PEDOT:PSS films in the fabrication of high-performance semitransparent organic solar cells.